Evaluasi Program Pendidikan Pengembangan Spesialisasi Bintara Dasar Intelijen (Densus 88 AT) - Yusdan Ibnuza Mahany; Suryadi Suryadi; Sugiarto Sutomo (Program Studi Manajemen Pendidikan, 2022)
This study aims to determine the impact of the Dikbangspes program for students and the agencies where students work, through a qualitative approach that seeks to reveal descriptively the evaluation of the program so as to obtain objective data to assess the achievement of the Dikbangspes Bintara Dasar Intelligence (Densus 88 AT) program. Data and information in the form of interviews, questionnaires, documentation studies, document analysis about the Basic Intelligence Non-commissioned Officer Specialization Development Education program (Densus 88 AT) at the Pusdik Intelkam Lemdiklat Polri will be processed and presented descriptively by conducting analysis using procedures based on 4 (four) stages of Kirkpatrick program evaluation which include evaluation: reaction, learning, behavior, and results. Reaction Evaluation Stage: In the curriculum component, in general, participants expressed satisfaction with this Dikbangspes curriculum. There needs to be integration between theory and practice. The results of the reaction evaluation of Dikbangspes participants are generally stated to have met the criteria for achieving the evaluation of the Dikbangspes program program to bring behavior change to its participants. Evaluation of the results of the evaluation of the results of the Dikbangspes has met the research criteria. The implications of this study need to evaluate the management of Dikbangspes for the future (2) Periodically evaluate each student's development both in the cognitive, affective, psychomotor, physical and psychological aspects of participants. In this pandemic era, this is very important because the psychological side will certainly have an impact on the absorption of Dikbangspes learning materials